Aroma precursors and methylpyrazines in underfermented cocoa beans induced by endogenous carboxypeptidase. - Selamat, Jinap; Y., Ikrawan; Bakar, Jamilah; Saari, Nazamid; Hanifah Lioe, Nuryani (Wiley-Blackwell, 2008)
Cocoa-specific aroma precursors and methylpyrazines in underfermented cocoa beans obtained from fermentation induced by indigenous carboxypeptidase have been investigated. Fermentation conditions and cocoa bean components were analyzed during 0 to 3 d of fermentation. Underfermented cocoa beans were characterized as having hydrophilic peptides and free hydrophobic amino acids much higher than unfermented ones. These 2 key components of cocoa aroma precursors may be produced from the breakdown of proteins and polypeptides by endogenous carboxypeptidase during the fermentation process. The enzyme was activated during fermentation. Polypeptides of 47, 31, and 19 kDa were observed in the samples throughout the 3-d fermentation period; however, only the first 2 polypeptides were remarkably reduced during fermentation. Since the 1st day of fermentation, underfermented cocoa beans contained methylpyrazines, a dominant group of cocoa-specific aroma. This might be due to microbial activities during fermentation, observed through a decrease of pH value and an increase of temperature of cocoa beans. The concentration of tetramethylpyrazines was significantly increased during the 3 d of fermentation. This may increase the cocoa-specific flavor to the beans.